Telaah Gagasan Paramadina tentang Pernikahan Beda Agama - Iffah Muzammil (Islamica: Jurnal Studi Keislaman, 2016)
This article deals with the idea of interfaith marriage proposed by the Endowment Foundation of Paramadina (Yayasan Wakaf Paramadina) established by Nurcholish Madjid and his colleagues. The activists of this foundation offer ideas to give freedom to every Muslim, both male or female, to marry a non-Muslim, regardless of their religion and their faith. This idea is at least starting from two basic assumptions; first, that the Qurâ€™Ã¢n only prohibits marriage with Arab polytheists which are almost certainly does not exist now; and second, that all religions and faiths that exist today are People of the divine Book. This idea had never been previously proposed by other scholars who only allow the marriage of male Muslim with woman from the people of the Book (Jews and Christians). Even the existing Indonesian law requires that marriage should be performed by a pair of co-religionists. This idea refers to the considerat-ion of social relationships, namely the creation of inter-religious harmony, but apparently tend to ignore the interests of the faith.